Isolation of peroxisome-deficient mutants of Saccharomyces cerevisiae. - Erdmann, R (1989)
Two mutants of Saccharomyces cerevisiae affected in peroxisomal assembly (pas mutants) have been isolated and characterized. Each strain contains a single mutation that results in (i) the inability to grow on oleic acid, (ii) accumulation of peroxisomal matrix enzymes in the cytosol, and (iii) absence of detectable peroxisomes at the ultrastructural level. These lesions (pas1-1 and pas2) are shown to be nonallelic and recessive. Crossing of pas1-1 and pas2 strains resulted in diploid cells that had regained the ability to grow on oleic acid as sole carbon source and to form peroxisomes. These pas mutants may provide useful tools for future studies on the molecular mechanisms involved in peroxisomal assembly.